National role conceptions in a new millennium: defining a place in a changing world - Grossman, Michael; Schortgen, Francis; Friedrichs, Gordon (Role theory and international relations, 2022)
Introduction : defining roles in a polycentric world / Michael Grossman, Francis Schortgen, and Gordon Friedrichs -- Shrinking the U.S. leadership role : populism and the change of domestic and international "others" / Sebastian Harnisch & Gordon Friedrichs -- The evolution of Russia's national role conceptions : from cooperation to great power competition / Michael Grossman -- A Chinese grand strategy in the making? : the 'China dream', the 'Belt and Road Initiative' and national role conceptualization in a changing world / Francis Schortgen -- A tenuous island : the destabilization of Britain's role in the international system of the 21st century / Spencer Whyte -- Berlin, we have a problem : explaining crises in US-German relations after the Cold War / Florian Böller -- Contesting Japan's international role : the responses of Japanese non-governmental organizations to the transformation of Japanese ODA policy / Kamila Szczepanska -- The EU's self-conception of its roles in global affairs / Rikard Bengtsson -- NATO's changing roles in a post-hegemonic order / Sebastian Mayer -- ASEAN : the center of Asian regionalization? : a model for a global future? / Joel Campbell -- The Organization of American States' role as facilitator of democracy promotion : persuasion and social influence during the political crisis in Venezuela / Gordon Friedrichs -- Conclusion : turbulence in the 21st century international order / Francis Schortgen, Gordon Friedrichs, and Michael Grossman.